Fine-scale changes in speed and altitude suggest protean movements in homing pigeon flights. Issue 5 (19th May 2021) - Garde, Baptiste; Wilson, Rory P.; Lempidakis, Emmanouil; Börger, Luca; Portugal, Steven J.; Hedenström, Anders; Dell'Omo, Giacomo; Quetting, Michael; Wikelski, Martin; Shepard, Emily L. C.
Abstract : The power curve provides a basis for predicting adjustments that animals make in flight speed, for example in relation to wind, distance, habitat foraging quality and objective. However, relatively few studies have examined how animals respond to the landscape below them, which could affect speed and power allocation through modifications in climb rate and perceived predation risk. We equipped homing pigeons ( Columba livia ) with high-frequency loggers to examine how flight speed, and hence effort, varies in relation to topography and land cover. Pigeons showed mixed evidence for an energy-saving strategy, as they minimized climb rates by starting their ascent ahead of hills, but selected rapid speeds in their ascents. Birds did not modify their speed substantially in relation to land cover, but used higher speeds during descending flight, highlighting the importance of considering the rate of change in altitude before estimating power use from speed. Finally, we document an unexpected variability in speed and altitude over fine scales; a source of substantial energetic inefficiency. We suggest this may be a form of protean behaviour adopted to reduce predation risk when flocking is not an option, and that such a strategy could be widespread.